Vegetative propagation of rare tree species for forest restoration - Anantika Ratnamhin (2018)
Nine rare tree species were selected for investigating their suitability for cuttings: 1) Crypteronia paniculata Bl. var. paniculata, 2) Diospyros coaetanea Flet., 3) Gardenia sootepensis Hutch., 4) Haldina cordifolia (Roxb.) Rids., 5) Ilex umbellulata (Wall.) Loesn., 6) Mesua ferrea L., 7) Rothmania sootepensis (Craib) Brem., 8) Schoutenia glomerata King ssp. peregrine (Craib) Roekm. & Hart., and 9) Scleropyrum pentandrum (Dennst.) Mabb. Five separate experiments were run to test the effect of various treatments; i) concentrations and forms of rooting hormones, ii) node positions iii) fungicide, iv) leaf area, and v) propagation media. None of these treatments were successful in producing viable planting stock in sufficient quantities, although limited success was achieved with Shoutenia glomerata. The best treatment was no hormone treatment (control), which produced the highest relative performance score (86.1%). It required almost 10 months from collecting cuttings to potting of rooted cuttings.